2013
DOI: 10.1016/j.nucmedbio.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and p53 are not involved in the anti-tumor efficacy of 125I-labeled monoclonal antibodies targeting the cell membrane

Abstract: Cell membrane sensitivity to (125)I-mAbs is not mediated by apoptosis and is p53-independent. Bystander effects-mediated mitotic death could be involved in the efficacy of (125)I-mAbs binding cell surface receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Boyd et al [66] observed similar killing of bystander HCT116 cells when they were treated with media harvested from either MIBG (accumulating within the cytoplasm) or IUdR (incorporating into DNA) labeled with either 131 I (low LET β-emitter), or 123 I (high LET Auger emitter). An independence of bystander effect generation of radionuclide sub-cellular location was also indicated by Paillas et al [67] for HCT116 p53-/-and p53+/+ colorectal carcinoma cells. The direct effects of 125 I-labeled monoclonal antibodies targeting the membrane bond, non-internalizing carcinoembryonic antigen (CEA), and internalizing, cytoplasm reaching epidermal growth factor receptor (HER1) were different; anti-CEA 125 I-mAbs were much more cytotoxic than anti-HER1 125 I-mAbs in both p53-/-and p53+/+ HCT116 cells.…”
Section: In Vitro Studies Of Radionuclide Induced Bystander Effectsupporting
confidence: 59%
“…Boyd et al [66] observed similar killing of bystander HCT116 cells when they were treated with media harvested from either MIBG (accumulating within the cytoplasm) or IUdR (incorporating into DNA) labeled with either 131 I (low LET β-emitter), or 123 I (high LET Auger emitter). An independence of bystander effect generation of radionuclide sub-cellular location was also indicated by Paillas et al [67] for HCT116 p53-/-and p53+/+ colorectal carcinoma cells. The direct effects of 125 I-labeled monoclonal antibodies targeting the membrane bond, non-internalizing carcinoembryonic antigen (CEA), and internalizing, cytoplasm reaching epidermal growth factor receptor (HER1) were different; anti-CEA 125 I-mAbs were much more cytotoxic than anti-HER1 125 I-mAbs in both p53-/-and p53+/+ HCT116 cells.…”
Section: In Vitro Studies Of Radionuclide Induced Bystander Effectsupporting
confidence: 59%
“…This protraction in inducing DSBs observed for short lived 188 Re can explain the equal efficacy of 188 Re-C1P5 and 177 Lu-C1P5 toward tumor growth arrest in spite of 1.4 times higher radiation dose to the tumor for 177 Lu-C1P5 than for 188 Re-C1P5 mAb. Observation of gamma H2AX staining several days after RIT administration emphasizes the different complex and protracted in time mechanisms involved in RIT effects on the tumor as even bystander cells in RIT experiments exhibit gamma H2AX staining [27] while in the case of external beam radiation, such staining can be observed only within hours post irradiation [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is most likely that the additional Auger and conversion electrons emitted by 161 Tb influenced the radiotoxicity too. The shortrange electrons exert their greatest toxicity effects only after internalisation or on the cell membrane of the target cell [30][31][32][33]. Inside the cell, Auger electrons are able to deposit high energy around the decay site which leads to ionisation and excitations, chemical transmutations, local effects of charged species, and nuclear recoil [30,34].…”
Section: Discussionmentioning
confidence: 99%